PANK2 and C19orf12 mutations are common causes of neurodegeneration with brain iron accumulation. Issue 2 (19th November 2012) - Dezfouli, Mitra Ansari; Alavi, Afagh; Rohani, Mohammad; Rezvani, Mohamad; Nekuie, Tayebeh; Klotzle, Brandy; Tonekaboni, Seyed Hasan; Shahidi, Gholam Ali; Elahi, Elahe
<x xml:space="preserve">Abstract</x> Background Neurodegeneration with brain iron accumulation (NBIA) constitutes a group of neurodegenerative disorders with pronounced iron deposition in the basal ganglia. PANK2 mutations are the most common cause of these disorders. C19orf12 was recently reported as another causative gene. We present phenotypic data and results of screening of PANK2 and C19orf12 in 11 unrelated Iranian NBIA patients. Methods Phenotypic data were obtained by neurologic examination, magnetic resonance imaging, and interviews. Mutation screening of PANK2 and C19orf12 was performed by sequencing. Results PANK2 and C19orf12 mutations were found in 7 and 4 patients, respectively. Phenotypic comparisons suggest that C19orf12 mutations as compared with PANK2 mutations result in a milder disease course. Conclusions Mutations in both PANK2 and C19orf12 contributed significantly to NBIA in the Iranian patients. To the best of our knowledge, this is the first genetic analysis reported on a cohort of NBIA patients from the Middle East. © 2012 Movement Disorder Society